IMPROVING SLOW LEARNER STUDENTS’ WORD RECOGNITION SKILL THROUGH GLOBAL METHOD ON BUDI MULIA DUA BINTARO ELEMENTARY SCHOOL’S THIRD GRADE STUDENTS - Indira Raissa Jasmine; Ishak G. Bachtiar; Leliana Lianty (Universitas Majalengka, 2024)
Reading may have been taught in the early grades, however it is not an easy task for students with special needs, especially those with slow learning problems. If slow learners have not fully mastered word recognition skills, which is a prerequisite for reading comprehension phase, they will fall behind and need constant help for their studies. Hence, this research aims to improve slow learners' word recognition skills using a global method. This research was held from October to November 2023, with the research subjects being slow learners at third class in elementary school. Classroom Action Research (PTK) with a Two-cycle Kemmis & McTaggart model was used as the method, which consists of three stages: planning, action + observation, and reflection. Results show that throughout the process, the slow learner students' word recognition skill increased slowly, gaining an average score of 45.66% to 83.55% when cycle II was implemented with the score of 75% as a minimum standard of success. The results concluded that the global method is suitable for students who are not yet fluent in reading and want to learn simple sentences and words because it teaches students to understand how sentences and words are formed so they do not only memorize them.